SUICIDE IN LATE LIFE: IDENTIFYING AND ADDRESSING RISK FACTORS. (11th November 2018) - Fiske, A; Conwell, Y
Abstract: Older adults are disproportionately likely to die by suicide, with older men being at the highest risk of any demographic group. To address this major public health problem, there is an urgent need to identify risk factors relevant to suicide in later life and to translate this knowledge into treatments that will reduce the risk of suicide in this age group. This symposium will present research on risk factors for suicide in late life as well as factors associated with the reduction of suicidal ideation among older men. First, Kimberly Van Orden, PhD, will present data on mortality outcomes for individuals endorsing death ideation or suicidal ideation. Then, Carol Leung, LCSW, will present a study that examined demographic characteristics and precipitating factors associated with firearm suicide among young, middle-aged and older women. Next, Amy Fiske, PhD, will present a case study that raises the possibility of a novel risk factor for late-life suicide. Then, Marnin Heisel, PhD, will present a study that tested whether personality moderates the effects of Meaning-Centered Men's Groups on suicidal ideation. Yeates Conwell, M.D., Director of Geriatric Psychiatry and Co-Director of the Center for the Study and Prevention of Suicide at the University of Rochester Medical Center, will serve as discussant.